Photocaged Arabinose: A Novel Optogenetic Switch for Rapid and Gradual Control of Microbial Gene Expression. (19th January 2016) - Binder, Dennis; Bier, Claus; Grünberger, Alexander; Drobietz, Dagmar; Hage‐Hülsmann, Jennifer; Wandrey, Georg; Büchs, Jochen; Kohlheyer, Dietrich; Loeschcke, Anita; Wiechert, Wolfgang; Jaeger, Karl‐Erich; Pietruszka, Jörg; et al.
Abstract: Controlling cellular functions by light allows simple triggering of biological processes in a non‐invasive fashion with high spatiotemporal resolution. In this context, light‐regulated gene expression has enormous potential for achieving optogenetic control over almost any cellular process. Here, we report on two novel one‐step cleavable photocaged arabinose compounds, which were applied as light‐sensitive inducers of transcription in bacteria. Exposure of caged arabinose to UV‐A light resulted in rapid activation of protein production, as demonstrated for GFP and the complete violacein biosynthetic pathway. Moreover, single‐cell analysis revealed that intrinsic heterogeneity of arabinose‐mediated induction of gene expression was overcome when using photocaged arabinose. We have thus established a novel phototrigger for synthetic bio(techno)logy applications that enables precise and homogeneous control of bacterial target gene expression. Abstract : Illuminating expression : Photocaged arabinose represents the first one‐step photocleavable bacterial inducer that allows fast, accurate, and homogeneous control of target gene expression. The novel phototrigger is independent of the target gene or secondary cellular reactions and thus suited for synthetic bio(techno)logy and single cell applications.